Experiential authenticity and spatial psychology: A Human-centered reading of the Jewish Museum Berlin - Htoo, Shwun Thwet (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: The Jewish Museum Berlin, designed by Daniel Libeskind, exemplifies a shift in contemporary museum architecture, where spatial design becomes a narrative tool to address cultural trauma and shape collective memory. As cities increasingly compete on cultural identity, architecture plays a growing role in city branding and emotional engagement. Methods: This study employs a mixed-methods approach, integrating qualitative interpretive analysis with quantitative survey data. Thematic coding using NVivo was applied to open-ended visitor responses, while descriptive statistics were used to analyze Likert-scale responses from 100 participants. Findings: Architectural features such as voids, fragmented pathways, and disorienting circulation elicit strong emotional engagement and embodied memory. These spatial experiences enhance the perceived authenticity of the museum and reinforce Berlin’s identity as a city of remembrance. Visitors rated the museum highly for emotional authenticity (M=4.29, SD=1.25; 71% agreement). Perceived authenticity strongly correlated with emotional engagement (r = 0.65, p <0.01) and with Berlin’s identity as a city of remembrance (r=0.71, p <0.01). High mean scores for embodied experience (up to M=4.46; 94% agreement) indicate that voids, tilted floors, and immersive acoustics evoke disorientation, reflection, and sensory resonance. NVivo coding reinforced these quantitative trends, revealing recurring themes of emotional immersion, embodied memory, authenticity, and urban identity reflection. Conclusion: Spatial and sensory design in the Jewish Museum Berlin contributes to emotionally authentic experiences that align with and strengthen Berlin’s urban identity and cultural narrative. Novelty/Originality of this article: This study contributes a human-centered analysis of how trauma-informed architecture can produce experiential authenticity and support city branding. By combining emotional psychology, spatial design theory, and urban identity, the paper offers a new interdisciplinary lens on affective architecture.